Market Structure and the Business Cycle - Jang-Ok Cho (Queen's University, Department of Economics, 1990)
The key ingredients of real business cycle models are common. The market structure is perfectly competitive, the forcing process is a technology shock, and in most cases agents are identical. Textbook market structures are introduced in a real business cycle model. The market structures studied are perfect competition, monopoly, oligopoly, and monopolistic competition. The results show that economy-wide monopoly or two-firm oligopoly with the technology shock of the size estimated by Prescott (1986) cannot produce the output volatility observed in the U.S. economy. However, ten-firm oligopoly can mimic the output volatility with the technology shock of the same size. Since an actual economy has much more than ten firms, it is argued that it is safe to used the competitive market structure in a study of business fluctuations. In addition, it is shown that market structure itself is not a mechanism magnifying the responsiveness of a model to a policy shock like government purchases.
Keywords: 330